Analisis Mutasi pada Kodon 531 Pada Gen Rpob Mycobacterium tuberculosis Penyebab Resistensi Rifampisin - Yatnita Parama Cita; Dwi Hilda Putri (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Tuberculosis (TB) is a serious disesase in the world. According to the WHO, it is estimated more than 3 million people die every year as a result of this infectious disease. One factor that causes diffi culty handling TB chemoteraphy is not effective against the bacteria Mycobacterium tuberculosis that causes TB . Effectiveness of treatment is often hampered by the emergence of bacterial resistance against M. Tuberculosis chemotherapy agents are given. From some research found that bacterial resistance may occur in more one type of chemotherapy agent also known as multi-drug resistance (MDR). Mycobacterium tuberculosis develop resistance mechanisms that are different from other bacteria in general. In prokaryotes, resistance is generally due to the transfer of genetic, either through plasmids,transposons and other. Reference sequence beta sub unit of RNAP protein M. Tuberculosis with accession number NP_215181.1 and M. tucerculosis rpoB gene with accession number NC_000962.3 used to obtain preliminary information from the data base www.ncbi.nlm.gov and www.uniprot.org . Mutation done according to several studies literature. Analysis of the composition, profi le, location and structure of protein using www.expasy.org, TMHMM and http://bioinf.cs.ucl.ac.uk/psipred. The primer design is done with Primer Design Program. Based on the analysis of mutation in the beta subunit of RNAP protein M. Tuberculosis, codon 531 (Ser ->Leu), it is known that mutations cause changes in some properties and structure of proteins. Possible changes affecting the nature of bacterial resistance to antibiotics rifampicin. However, further analysis needs to be done with the analysis of the docking technique.